(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article investigates the improvement of industrial equipment performance efficiency using Computational Fluid Dynamics (CFD) simulations and evaluates its economic impact. The study focuses on analyzing fluid flow behavior, heat transfer processes, and energy losses in industrial equipment such as pumps, turbines, compressors, and heat exchangers. In modern industrial systems, equipment efficiency directly influences energy consumption, operational costs, and overall productivity. Inefficient flow design, turbulence, and thermal losses often lead to significant energy waste. CFD-based simulation provides a powerful tool to analyze these physical phenomena in detail and optimize equipment performance before physical implementation. The results of this study show that CFD-based optimization significantly improves equipment efficiency, reduces energy losses, and provides substantial economic benefits through reduced operating and maintenance costs.